The coroner. Season two [videorecording (DVD)] - Szkopiak, Piotr, 1966-; Carter, Matt (Television director); Goose, Claire, 1975-; Bardock, Matt; Edney, Beatie, 1962- (BBC, 2018)
A coroner and a detective investigate sudden and unexplained deaths.